2014
DOI: 10.1186/s40712-014-0018-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of NiTe2 thin films with the influence of amino additives

Abstract: Background: Nickel, one of the transition metals synthesised with chalcogenides such as Se, S and Te with possible combinations of nickel chalcogenides such as NiS 2 , NiSe, NiSe 2 and Ni 3 Se 2 . The combination of nickel and telluride are the fewest being observed due to the nature of tellurium that is relatively heavier than both sulphur and selenium, thus poorly-adhesive onto the substrate. Methods: Therefore, NiTe 2 thin film is being synthesised onto the indium tin oxide (ITO) coated glass substrates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The double side-tungsten inert gas weldments show lowest absorbed energy 119.0 J compared to base metal 123.17 J. This is because of the existence of higher induced δ-ferrite in the weld metal [31,32]. The samples could not entirely break in the notched area.…”
Section: Impact Testmentioning
confidence: 94%
“…The double side-tungsten inert gas weldments show lowest absorbed energy 119.0 J compared to base metal 123.17 J. This is because of the existence of higher induced δ-ferrite in the weld metal [31,32]. The samples could not entirely break in the notched area.…”
Section: Impact Testmentioning
confidence: 94%
“…Elsewhere, nickel sulfides and nickel selenides were most investigated by researches . Another analogue of nickel tellurides, which profits from the metallic feature of tellurium, is of fundamental interest in their own right but also for their potential technological relevance. Considerable recent research related to transition metal telluride, including CoTe 2 , NiTe 2 , MnTe 2 , NiTe, and CoTe, have been performed in electrocatalysis applications. As concluded previously, both transition metal monotellurides and ditellurides are capable to electrocatalysis in alkaline solution. However, more sophisticated design and controllable synthesis of monotellurides and ditellurides are required in experiment, especially for developing improved bifunctional electrocatalysts.…”
Section: Introductionmentioning
confidence: 96%
“…Anand et al . have found that the acidic electrolyte is not suitable for depositing NiTe 2 thin film through electrochemical route . The present work deals with the fabrication of NiTe NRs by hydrothermal process for supercapacitor applications.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Magnetic phase transition in NiTe x from paramagnetic (x = 1) to diamagnetic (x = 2) has been reported by Lie et al [27] Anand et al have found that the acidic electrolyte is not suitable for depositing NiTe 2 thin film through electrochemical route. [28] The present work deals with the fabrication of NiTe NRs by hydrothermal process for supercapacitor applications. NiTe NRs exhibit a high specific capacitance of 618 F g À 1 and 1 A g À 1 current density with an outstanding cyclic stability of 75% of initial specific capacitance after 5000 cycles at a high current density of 10 A g À 1 .…”
Section: Introductionmentioning
confidence: 99%